Alternative Frequency Selection of Long Term Evolution (LTE) Technology in Indonesia - Uke Kurniawan Usman; Galuh Prihatmoko (UIN Sultan Syarif Kasim Riau, 2011)
AbstractFrequency is a limited resource that is indispensable for cellular telecommunications. Frequency allocation needs to be done from the beginning that there was no interference between cellular technology. Frequency allocation policy is one factor inhibiting adoption of Long Term Evolution technology in Indonesia. Based on standard ITU-R, 3GPP, APAC conference, as well as the frequency of the condition in Indonesia. There are several candidate frequency can be allocated to LTE technology, namely: 700MHz,2.1GHz,2.3 GHz and 2.6GHz frecuency. After review of the analysis result produced a recommendation for LTE frequency allocation in Indonesia, is 700MHz frecuency. However, if the use of 700 MHz frequency has 700MHz frecuency constraint is currently still used for TV broadcast frecuency. So using 700MHz frequency can be implemented for LTE technology is carried out after the TV broadcast frequency has been re-farming to digital TV. Keywords: LTE, Frequency, 3GPP.